An open-source active power controller for grid required ancillary services - Nadia Zendehdel; Danyal Bustan (Universitas Ahmad Dahlan, 2022)
With increasing penetration of renewable energies into modern power systems, supporting grid required ancillary services become a challenging problem. Wind turbines, as one of the main sources of renewable energies, has some inherit features which can be employed to support ancillary services for utility grids. One of the key requirements of grid operators is active power control for frequency regulation. But this requirement cannot be addressed with traditional wind turbine controllers as these controllers try to capture maximum of available power while with active power control, the output power should be limited to a predefined (time varying) set-point. Although new methods are introduced for active power control, there is no suitable comparison between them because of lack of a standards and easy to implement tools. In this paper, an extension to well-known open source reference open-source controller (ROSCO) controller based on the national renewable energy laboratory (NREL) 5 mega watt (MW) fatigue, aerodynamics, structures, and turbulence (FAST) model is proposed to support active power control. With this extension, in addition to active power control support the resulted mechanical loads on various turbine parts can be evaluated